2020
DOI: 10.1371/journal.pone.0228289
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of classification performance of Parkinson’s disease using shape features for machine learning on dopamine transporter single photon emission computed tomography

Abstract: Objective To assess the classification performance between Parkinson's disease (PD) and normal control (NC) when semi-quantitative indicators and shape features obtained on dopamine transporter (DAT) single photon emission computed tomography (SPECT) are combined as a feature of machine learning (ML). Methods A total of 100 cases of both PD and normal control (NC) from the Parkinson's Progression Markers Initiative database were evaluated. A summed image was generated and regions of interests were set to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Studies using DAT-SPECT scans and various computational techniques have shown excellent performance with high accuracy in the classification of parkinsonism patterns [ 22 , 23 , 24 , 25 , 26 ]. The accuracy of the Faster R-CNN in distinguishing the PD pattern from other patterns was comparable to previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using DAT-SPECT scans and various computational techniques have shown excellent performance with high accuracy in the classification of parkinsonism patterns [ 22 , 23 , 24 , 25 , 26 ]. The accuracy of the Faster R-CNN in distinguishing the PD pattern from other patterns was comparable to previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent machine-learning studies using quantitative parameters, such as the striatal binding ratio of DAT-SPECT, showed high accuracy in the classification of PD [ 24 , 25 , 30 ]. The use of quantitative analysis is more objective than relying on visual analysis alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent studies have provided promising results demonstrating that ML improves classification performance of dopamine transporter single photon emission computed tomography images for the differentiation of PD from other parkinsonian disorders, potentially shortening the diagnostic delay in our case of YOPD. 11,12 This application could be implemented in underserved regions assisting a remote radiologist to interpret advanced neuroimages, leading to an earlier and more accurate diagnosis of PD, especially in the early stage when characteristic features to confirm or refute the diagnosis are quite subtle and neither sensitive enough to be observed by clinical examination (eg, subtle red flags) nor specific enough for clinical interpretation (eg, a less defined dopaminergic response). 13…”
Section: Ai In the Diagnosis Of Pdmentioning
confidence: 99%
“…Recently, in 2020 Shiiba et al [86] present an approach to classify PD patients and HC subjects based on SBRs, shape and intensity features from DAT-SPECT images. These features are combined and used as input for the SVM classifier.…”
Section: Binary Classification Of Pd Patients and Hc Subjectsmentioning
confidence: 99%